2014
DOI: 10.1371/journal.pone.0094118
|View full text |Cite
|
Sign up to set email alerts
|

Expression of RAGE and HMGB1 in Thymic Epithelial Tumors, Thymic Hyperplasia and Regular Thymic Morphology

Abstract: Recently, a role of the receptor for advanced glycation endproducts (RAGE) in myasthenia gravis was described. RAGE and its ligand high mobility group box 1 (HMGB1) play key roles in autoimmunity and cancer. To test whether these molecules are involved in patients with thymic abnormalities we applied immunohistochemical analysis in 33 cases of thymic epithelial tumors, comprising 27 thymomas and 6 thymic carcinomas, and 21 nonneoplastic thymuses. Both molecules were detected in neoplastic epithelial cells: RAG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 64 publications
4
31
0
Order By: Relevance
“…20 RAGE is also expressed in neurons and glial cells of the brain, and its expression can be unregulated by activated astrocytes and microglia cells. 8 In a mouse model of ischemia/reperfusion injury in heart, HMGB1 binds to RAGE soon after injury and thereby activates proinflammatory pathways and exacerbates myocardial injury.…”
Section: Discussionmentioning
confidence: 99%
“…20 RAGE is also expressed in neurons and glial cells of the brain, and its expression can be unregulated by activated astrocytes and microglia cells. 8 In a mouse model of ischemia/reperfusion injury in heart, HMGB1 binds to RAGE soon after injury and thereby activates proinflammatory pathways and exacerbates myocardial injury.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have reported that estrogen is involved in biological functions in human and animal organs through estrogen receptors, including ERα and ERβ (which has at least five isoforms, such as ERβ5) (22)(23)(24). At present, controversial findings exist on the expression of estrogen receptors in thymic tumors, since a number studies reported overexpression of ERβ in these tumors, whereas others studies obtained contradictory results (11,12,13,19).…”
Section: Discussionmentioning
confidence: 99%
“…To establish the negative controls, the same procedure was followed, without the primary antibody. A previously described scoring system was adopted (19), the tissue microarrays were digitized and cytoplasmic ERβ5 (cERβ5) or nuclear ERβ5 (nERβ5) immunoreactivity was scored between -and +++ (-, no staining; +, weak staining; ++, moderate staining; +++, strong staining). The percentage of tumor cells displaying staining for cERβ5 or nERβ5 was determined and calculated as the average of six high power fields per specimen.…”
Section: Immune Microarray and Evaluation Of Immunoreactivitymentioning
confidence: 99%
“…HMGB1, expressed in 55.6% of the colorectal cancer (CRC) patients, is significantly correlated with lymph node metastases and pathological stage (15). HMGBI expression is elevated in thymic epithelial tumors involved in the pathology and physiology of thymus (16). High expression ofHMGB 1 activates Tregs and Th2 polarization, promoting the immune evasion and the recurrence of HPV infection in cervical cancer (17).…”
Section: Fig 3 Kaplan-meier Analysis Of Overall Survival Rate Ofgasmentioning
confidence: 99%